2022
DOI: 10.1038/s41598-022-10182-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment-aware, single-transcriptome prediction of microsatellite instability in colorectal cancer using meta-analysis

Abstract: Detecting microsatellite instability (MSI) in colorectal cancers (CRCs) is essential because it is the determinant of treatment strategies, including immunotherapy and chemotherapy. Yet, no attempt has been made to exploit transcriptomic profile and tumor microenvironment (TME) of it to unveil MSI status in CRC. Hence, we developed a novel TME-aware, single-transcriptome predictor of MSI for CRC, called MAP (Microsatellite instability Absolute single sample Predictor). MAP was developed utilizing recursive fea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…We inferred microsatellite instability status by running Microsatellite instability Absolute single sample Predictor (MAP) 74 on pseudo-bulk generated from our ST samples (see section Pseudo-bulk generation). They were classified as microsatellite instable (MSI) or microsatellite stable (MSS).…”
Section: Methodsmentioning
confidence: 99%
“…We inferred microsatellite instability status by running Microsatellite instability Absolute single sample Predictor (MAP) 74 on pseudo-bulk generated from our ST samples (see section Pseudo-bulk generation). They were classified as microsatellite instable (MSI) or microsatellite stable (MSS).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we found that the dmPIRs tagging the MLH1 gene and the EPM2AIP1 gene overlapped. These two genes are encoded on opposite strands of the chromosome, both functioning as tumor suppressors in colorectal cancer ( 50 , 51 ). The methylation level of their TSS inversely correlated with gene transcriptional levels (Figure 6C, D ).…”
Section: Resultsmentioning
confidence: 99%
“…7 a) with effectiveness approaching TIDE, MSI.Score, and others (Additional file 7 : Fig S7b). Considering that TIDE [ 56 ], MSI.Score (microsatellite instability) [ 87 , 88 ], TMB (tumor mutational burden) [ 89 92 ], CD274 [ 93 ], CD8 [ 94 ], IFNG (IFNγ) [ 95 ], T.Clonality [ 96 ], B.Clonality [ 97 ] and Merck18 (T-cell-inflamed signature) [ 95 ] were constructed for the purpose of predicting response to ICB, and the recent FDA approval granting the use of pembrolizumab (PD1 blockade) therapy for solid tumors in adults with high MSI and TMB score [ 63 ], the matching efficacy of Overlap36 validates its potential as a novel predictor of cancer response to ICB.
Fig.
…”
Section: Resultsmentioning
confidence: 99%